How do Social Media Influencers Trigger Impulse Buying: The Mediating Role of Emotional Arousal and Cognitive Bias - Monisha, L.; Chellamuthu, Sahila (International Review of Management and Marketing, 2026)
Dual Process Theory and the Elaboration Likelihood Model inform this study, which investigates the psychological mechanisms by which social media influencer posts lead to impulse purchasing. In particular, the research investigates the relationship between social media influencer content exposure and impulse purchasing behavior, an area that has been researched very little in consumer behavior literature. It does this by investigating the dual mediation influence of emotional arousal and cognitive bias. 412 Indian social media users filled out a standardized questionnaire, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the data. The model examines both the direct and indirect effects to test the hypothesized dual-path mediation model. Results indicate that content created by influencers positively and significantly influences impulse buying behavior. Emotional arousal and cognitive bias were found to mediate this relationship, as hypothesized in this study through the dual psychological pathway. Influencer marketers must be aware of the cognitive and affective processes hidden in influencer posts and design campaigns appropriately, taking advantage of these mechanisms. Insights also have implications for consumer protection policy on the internet. The study contributes to influencer marketing and consumer psychology literature by empirically examining and determining a dual-mediation model and presenting a deeper insight into the mechanisms through which influencer posts drive impulse buying through affective and heuristic routes.